2021
DOI: 10.18662/rrem/13.4/496
|View full text |Cite
|
Sign up to set email alerts
|

Authentic Social-Cultural Reading in Foreign Language Learning and Teaching

Abstract: The paper concerns the use of authentic social-cultural reading materials in foreign language learning and teaching of international students. The study was started from the assumption that authentic materials allow international students to link mastering a foreign language and the real world since they meet learners’ needs and contribute to better social adaptation in a foreign country. The purpose of the article is to characterize the place and role of work with authentic social-cultural reading materials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
0
0
Order By: Relevance
“…The selection of topics related to modern media for target language curriculum development is in accordance with the research findings in the field. Educators have observed that students exhibited a noticeable interest in using diverse digital and media resources and have been enthusiastic about acquiring the necessary knowledge and skills to consume and disseminate content safely and efficiently (Gómez Jiménez & Gutiérrez, 2019;Lushchyk et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The selection of topics related to modern media for target language curriculum development is in accordance with the research findings in the field. Educators have observed that students exhibited a noticeable interest in using diverse digital and media resources and have been enthusiastic about acquiring the necessary knowledge and skills to consume and disseminate content safely and efficiently (Gómez Jiménez & Gutiérrez, 2019;Lushchyk et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Theme 2: (Klimova, 2021;Lushchyk et al, 2021) stated that regarding teaching methods there is high demand for the use of authentic materials and teaching is almost the same as teaching business language because learners are professionals who should be provided with materials related to real-life scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…Reading authentic texts contributes to the development of communicative foreign language competence at the following levels: lingvistic, speech, socio-cultural, compensatory, training-cognitive (Lushchyk et al, 2021). It is important to mix methods of teaching because it is a way to keep interest in studies during the whole lecture.…”
Section: Discussionmentioning
confidence: 99%
“…The abundance of media resources provides teachers with a unique opportunity to teach EFL on authentic materials to their students. However, it should go along with critical literacy practice resources, namely, theoretical basis and critical media literacy principles, material and media selection, student characteristics and language level, students' and educators' skills to analyze credible information sources, their ability to process information, analyze and critique text, produce and distribute information (Afrilyasanti, Basthomi, Zen, & Fauziah, 2023;Lushchyk, Pikulytska, & Tsyhanok, 2021;McDougall, Supa, van Driel, & Sternadel, 2018). After the series of English-language media literacy and critical thinking trainings focusing on Ukrainian and EU media space correlation, substantial feedback was obtained through Google Forms, aimed to assess the attitudes of Ukrainian HEI students towards media literacy and critical thinking development in the context of EFL learning.…”
Section: Need For Media Literacy Education and Eu Experiencementioning
confidence: 99%